2014
DOI: 10.3390/ijerph110908984
|View full text |Cite
|
Sign up to set email alerts
|

Strong Associations Between the Pesticide Hexachlorocyclohexane and Type 2 Diabetes in Saudi Adults

Abstract: Pesticide exposure has been implicated as an environmental risk factor for the development of type 2 diabetes mellitus (T2DM). The aim of this study was to investigate the association of the body burden of the pesticide hexachlorocyclohexane (HCH) with the risk of T2DM in a sample of adults from Saudi Arabia. Serum samples were obtained from 280 adult subjects. Hexachlorocyclohexane isomer residues were measured by high-resolution gas chromatography-mass spectrometry. Data on lifestyle, dietary habits, and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 46 publications
0
7
0
2
Order By: Relevance
“…There are no prior studies of this association in a UK population. A link between β -HCH and preexisting type 2 diabetes has also been reported in cross-sectional studies involving Americans [ 22 , 23 ], Koreans [ 26 ], Slovakians [ 27 ], Saudi Arabians [ 30 ], and Norwegians [ 31 ]. Again, there are no prior studies of this association in a UK population.…”
Section: Discussionmentioning
confidence: 70%
“…There are no prior studies of this association in a UK population. A link between β -HCH and preexisting type 2 diabetes has also been reported in cross-sectional studies involving Americans [ 22 , 23 ], Koreans [ 26 ], Slovakians [ 27 ], Saudi Arabians [ 30 ], and Norwegians [ 31 ]. Again, there are no prior studies of this association in a UK population.…”
Section: Discussionmentioning
confidence: 70%
“…The pathogenesis of type 2 diabetes mellitus (T2DM) involves impairments in insulin resistance and secretion, which stems from both genetic and environmental causes. Various studies in adults have suggested that exposure to POPs is associated with T2DM (Airaksinen et al 2011; Al-Othman et al 2014; Lee et al 2011; MacNeil et al 2009; Philibert et al 2009; Tang et al 2014; Taylor et al 2013; Turyk et al 2009, 2015; Wu et al 2013). Several possible underlying mechanisms and/or pathways linking POPs to T2DM have been suggested, including potential involvement of POPs in insulin secretion or sensitivity; however, the complete picture is not yet understood fully.…”
Section: Introductionmentioning
confidence: 99%
“…Within the last decade numerous publications have reported positive associations between exposure to POPs and T2D incidence (A. Al-Othman et al 2014;A. A. Al-Othman, Abd-Alrahman, and Al-Daghri 2015;Arrebola et al 2013;Cappelletti et al 2016;Eslami et al 2016;Everett and Matheson 2010;Everett and Thompson 2012;Gasull et al 2012;Han et al 2020;Huang et al 2015;D.…”
Section: Emerging Links Between Pops and T2d Pathogenesismentioning
confidence: 99%